2013
DOI: 10.1016/j.meatsci.2013.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects on performance and carcass and meat quality attributes following immunocastration with the gonadotropin releasing factor vaccine Bopriva or surgical castration of Bos indicus bulls raised on pasture in Brazil

Abstract: Bos indicus bulls 20 months of age grazed on pasture in Minas Gerais, Brazil either received 2 doses of the GnRF vaccine Bopriva at d0 and d91 (group IC, n=144) or were surgically castrated on d91 (group SC, n=144). Slaughter on d280, was 27 weeks after castration. Adverse safety issues in 8% of group SC bulls following surgery contrasted with 0% in group IC bulls. At d105 testosterone levels were suppressed to similar levels in both groups. Importantly, group IC bulls had higher live weight, hot carcass weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
28
1
24

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 21 publications
12
28
1
24
Order By: Relevance
“…Another important management use of castration is the prevention of unwanted pregnancies; whether it be in mixed herds intended for slaughter, the accidental breeding of stud animals by those males not intended for breeding purpose, or population control (Ladd et al, 1994). The control of indiscriminate breeding becomes particularly important in the livestock industry when prolonged finishing of slaughter animals is required, such as in extensive systems, where male animals may reach puberty prior to slaughter (Amatayakul-Chantler et al, 2013). This is typically experienced when free-range animals are the end product.…”
Section: Motivation For Castrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important management use of castration is the prevention of unwanted pregnancies; whether it be in mixed herds intended for slaughter, the accidental breeding of stud animals by those males not intended for breeding purpose, or population control (Ladd et al, 1994). The control of indiscriminate breeding becomes particularly important in the livestock industry when prolonged finishing of slaughter animals is required, such as in extensive systems, where male animals may reach puberty prior to slaughter (Amatayakul-Chantler et al, 2013). This is typically experienced when free-range animals are the end product.…”
Section: Motivation For Castrationmentioning
confidence: 99%
“…Complications and the associated financial implications regarding physical castration can be prevented using immunocastration. Amatayakul-Chantler et al (2013) reported that adverse issues were experienced in 8 % of surgically castrated bulls raised on pasture, while those bulls immunocastrated experienced no complications related to the castration procedure. It is for these aforementioned reasons that alternatives to physical castration be investigated, while still controlling the problems associated with intact male production and preventing the welfare issues associated with both intact male and castrate production.…”
Section: Concerns With Castrationmentioning
confidence: 99%
“…(mANellA e BoIN, 2002;moreIrA et al, 2015). Antagonistas de GnRH induzem a rápida e profunda supressão da secreção de gonadotrofina, sendo que sua administração prolongada faz o controle do comportamento sexual devido à redução da testosterona, provoca a redução no tamanho dos testículos e a produção espermática, estabelecendo um quadro de infertilidade (HAYdeN, 2008), além de aumentar o potencial de produtividade dos animais (Huxsoll et al, 1998;roçA et al, 2011;JANeTT et al, 2012a;AmATAYAkul-cHANTler et al, 2013;mArTI et al, 2015). Estes antagonistas são cada vez mais utilizados para modular a fertilidade, comportamento e a produtividade dos machos, inclusive na castração dos animais (AdAms, 2005;ANdreo et al, 2013).…”
Section: Introductionunclassified
“…Amatayakul-Chantler et al ( 2013) informaram que níveis baixos a moderados de testosterona podem ter sido suficientes para exercer efeitos benéficos sobre a taxa de crescimento, peso vivo final e peso de carcaça quente.…”
Section: Análises Estatísticasunclassified
“…Nos animais CC, a castração foi realizada aos 12 meses de idade, retirando a função testicular e seu efeito anabólico, e por isso os animais Alguns trabalhos não observaram efeito na deposição de gordura nas carcaças avaliadas por ultrassonografia em animais terminados em confinamento entre as três condições sexuais (COOK et al, 2000;RIBEIRO et al, 2004;AMATAYAKUL-CHANTLER et al, 2013;MIGUEL et al, 2014 R. Ashmore et al, 1973;C. R. Ashmore et al, 1972;Lawrie, 1958) Os resultados encontrados no nosso estudo, foram similares aos observados por Miguel et al (2014) CARPENTER, 1978;MORGAN et al, 1993;KOOHMARAIE, 1994;EILERS et al, 1996).…”
Section: Características De Carcaça Avaliadas Por Ultrassomunclassified